Concatenated Attention: A Novel Method for Regulating Information Structure Based on Sensors - Zeyu Zhang; Tianqi Chen; Yuki Todo (Applied Sciences)
This paper addresses the challenges of limited training data and suboptimal environmental conditions in image processing tasks, such as underwater imaging with poor lighting and distortion. Neural networks, including Convolutional Neural Networks (CNNs) and Transformers, have advanced image analysis but remain constrained by computational demands and insufficient data. To overcome these limitations, we propose a novel split-and-concatenate method for self-attention mechanisms. By splitting Query and Key matrices into submatrices, performing cross-multiplications, and applying weighted summation, the method optimizes intermediate variables without increasing computational costs. Experiments on a real-world crack dataset demonstrate its effectiveness in improving network performance.